2019
DOI: 10.1111/ics.12551
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the use of antioxidants in anti‐ageing cosmetics

Abstract: Objective Skin health and beauty are a cornerstone of general well‐being in humans. Anti‐ageing cosmetics are used to provide a healthy and youthful appearance. Among the different cosmetic actives, antioxidants are incorporated in anti‐ageing products due to their beneficial effects in preventing and minimizing the signs of skin ageing. This work aims to understand how anti‐ageing formulations changed in the past 7 years regarding pure antioxidants composition. Methods Data were collected from anti‐ageing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 60 publications
0
48
0
4
Order By: Relevance
“…Even though EA is a compound widely used in topical products (Jeon et al, 2016, Silva et al, 2019), surprisingly, its physicochemical properties have not been reported to date. Additionally, the skin permeation profile of EA has not been investigated nor have the effects of different vehicles on skin uptake of EA been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Even though EA is a compound widely used in topical products (Jeon et al, 2016, Silva et al, 2019), surprisingly, its physicochemical properties have not been reported to date. Additionally, the skin permeation profile of EA has not been investigated nor have the effects of different vehicles on skin uptake of EA been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The use of anti‐aging cosmetics with vitamin C has increased in the last decade mainly due to their beneficial effects in preventing and minimizing the signs of skin aging 39 . The topical application of cosmetic goods containing 5%‐20% vitamin C promotes facial rejuvenation reducing wrinkles and erythema and increasing skin elasticity in volunteers 40‐42 .…”
Section: Discussionmentioning
confidence: 99%
“…These antioxidants have the ability to slow down the rate of oxidation, but they are not able to convert reactive species to more stable products. This type of antioxidant can chelate pro-oxidants metals and deactivate them, replenish hydrogen to primary antioxidants, deactivate single oxygen, act as scavengers, or absorb UV radiation [77]. According to Esfandi et al [78], there are two main mechanisms by which antioxidant molecules can deactivate free radicals: hydrogen atom transfer (HAT) and single electron transfer (SET).…”
Section: Role Of Hydrolyzed Collagen As An Antioxidant Ingredientmentioning
confidence: 99%